Endovascular Management for Accidental Cannulation of the Left Ascending Lumbar Vein with an Extracorporeal Membrane Oxygenation Catheter: A Case Report - Eui Hyun Yu; Jung Won Kim (Journal of the Korean Society of Radiology)
The femoral vein is frequently used for central venous access during extracorporeal membrane oxygenation (ECMO). Accidental cannulation of the ascending lumbar vein (ALV) during ECMO has rarely been reported. Hemorrhage related to venous rupture, or solid organ injury can occur depending on the course of the large-bore catheter. Ultrasonographic or fluoroscopic guidance helps ensure correct placement. Nevertheless, if accidental cannulation occurs, endovascular management can be considered a treatment option. We present the case of a 78-year-old man with an ECMO catheter malpositioned through the left ALV, which was removed with tract embolization.